Light- and pH-Controlled Hierarchical Coassembly of Peptide Amphiphiles - Wang, Dong (Langmuir : the ACS journal of surfaces and colloids, 2019)
The coassembly behavior of peptide amphiphiles (PAs) C4-Bhc-EE-NH2 and C14-FKK-NH2 has been investigated by transmission electron microscopy, atomic force microscopy, fluorescence microscopy, circular dichroism, Fourier transform infrared spectroscopy, and 1H nuclear magnetic resonance. These two PAs coassembled into nanofibers by electrostatic and π-π stacking interactions at a low concentration and further aggregated into nanofiber bundles via charge complementation on the surface of nanofibers. As the charge number varied with pH, the bundles could be disassembled/assembled with pH regulation. More interestingly, as C4-Bhc-EE-NH2 was a photodegradable molecule, the bundles could also be responsive to both ultraviolet (UV) and near-infrared (NIR) light. In contrast to the reversible pH-dependent response, the light responses were irreversible as C4-Bhc-EE-NH2 broke under UV or NIR radiation. The highlight of this article is that structural changes were realized for control at the aggregate level, not only at the molecular level. With this inspiration, we hope that we can support the novel biomaterial construction and exploitation of new functions of biomaterials